Plasma rich-platelet (PRP) potentially attenuates tamoxifen spermatogenic dysfunction in rat's model: sperm quality, histomorphometric, and apoptosis assessment - Hossein Hamali; Fatemeh Masoumi; Behzad Baradaran; Gholamreza Hamidian (Asia Pacific Journal of Medical Toxicology)
Background: Tamoxifen induces testicular atrophy and azoospermia. Conversely, platelet-rich plasma (PRP) is a distinctive analog yield enriched with cytokines and growth factors for improving tissue regeneration. Thus, this present study explored the roles model of PRP on production of sperm via apoptosis of tamoxifen-induced toxicity.Methods: Animals at 48 days' post- normal saline treatment and intra-testicular injection of normal saline (0.2 ml, left testis) as a single dose per week for two weeks. Infertility was induced by the oral administration of tamoxifen [0.6 mg/kg b.wt/day], and was then allocated into three groups: tamoxifen: oral administration of tamoxifen for 14 consecutive days, and intra-testicular injection normal saline; PRP: intra-testicular of 10 μl PRP, single dose; and tamoxifen + PRP.Results: Tamoxifen-injured rats showed significantly lower body weight, food intake, testicular weight and volume, LH and testosterone concentrations, production of sperm indices, and sperm motility considering the vehicle group. Tamoxifen-induced seminiferous tubular atrophy and testicular damages. Meanwhile, tamoxifen upregulated markers of apoptotic marker genes.Conclusion: In sum, the PRP supplement is potentially an impressive method for modifying production of sperm dysfunction via tamoxifen damages.